Improving Spatial Resolution Of Satellite Image Using Data Fusion Method - Muhsin, Israa; Mashee, Foud (Iraqi Journal of Science, 2024)
While many remote sensing and GIS applications require both the spatialresolution and spectral resolution be high, image fusion, or in other words, imagesharpening, is a useful technique. To date, numerous image fusion techniques havebeen developed to combine the clear geometric features of the panchromatic imageand the color information of the multispectral image. This paper compares theresults of four different pixel based fusion techniques, HLS, Broveytransformation,Gram–Schmidt and HSV techniques used to merge the ETM+multispectral image with (28.5 m)spatial resolution and panchromatic imagecaptured by SPOT satellite with (10m) spatial resolution, correlation coefficient ,root mean square error and peak signal to noise ratio criteria have been used toachieve the comparison among the using techniques